Chronic breathlessness: re-thinking the symptom. Issue 1 (25th January 2018) - Johnson, Miriam J.; Yorke, Janelle; Hansen-Flaschen, John; Lansing, Robert; Ekström, Magnus; Currow, David C.
We agree with much presented in O.K. Faull and colleagues' response to our proposed chronic breathlessness syndrome and thank them for their views supporting chronic breathlessness as more than just a symptom [1]. In particular, we agree that naming and defining chronic breathlessness as a syndrome does not aim, or need, to constrain a recognition or understanding of quantitative and qualitative between-individual differences. We agree that our intention is to ensure patients and their families living with the daily disability affecting all domains of life, irrespective of cause, may legitimately bring this experience to the attention of health and social professionals, receive a systematic assessment and subsequently benefit from individually tailored evidence-based management. Chronic breathlessness reaches beyond symptom perception into the realm of functional impairment and disability http://ow.ly/IBRd30h1wmS